Evaluación de pentacloronitrobenceno (PCNB) en el control de la pudrición radicular cusada por Rhizoctonia solani Kuhn en frijol común (Phaseolus vulgaris L.) - Pichardo Guido, Sergio (Agronomía Mesoamericana, 2016)
This experiment was conducted at “La Compañía”, Estación Experimental del Instituto Superior de Ciencias Agropecuarias (ISCA), which is located in the department of Carazo, Nicaragua. The trial was conducted during the months of June through September, 1987 with the following objectives: 1) To determine the appropiate rate of pentachloronitrobenzene (PCNB) for control of Rhizoctonia solani in common beans, 2) To evaluate the effect of mixing PCNB and “ Metalaxyl” on grain yield of common beans, 3) To determine yield reduction percentages caused by R. solani in common beans and 4) To select the best common bean variety in this experiment relative to the defined treatments. The results demonstrated that PCNB applied at a rate of 6.81 kg/ha was 3 % higher than the check and 12% higher than the highest rate of PCNB (11.36 kg/ha). The variety “Revolución 84” provided the highest yields compared to other entries.